Psychometric properties of the perceived vulnerability of diseases scale in South African teenagers during the covid-19 outbreak - Dolo, Selwin (My University, 2024)
Few factors throughout human evolutionary history have impacted human behaviour more than the effect of pathogens and infections as regards our adaptation and survival. To this end, human beings have evolutionary systems to preserve human existence and interact daily with pathogens. The behavioural immune system (BIS) and attachment functions are such evolutionary systems that humans use to perceive and avoid what may be of threat to their survival. This study examined the factor structure and cross-cultural validity of the Perceived Vulnerability to Disease Scale (PVD), a measure of the BIS system, in a sample of South African teenagers (N = 474; Age: M = 16.96 [SD = 1.31; range = 14 – 22yrs]). The PVD is important as it assists in understanding individual’s perceptions of infections, hence assisting in public health interventions. Varying CFA models (unidimensional and bidimensional models) were evaluated and cross-validated with Rasch analysis. The results showed that the PVD had a two-factor structure (Perceived Infectibility [PI] and Germ Aversion [GA]) in South African teenagers. Among other results, the findings show that the PVD measures perceived infectability equivalently across gender groups. Furthermore, the study highlights the impact of culture on the reliability of the measure.
Thesis ( M. A. (Clinical Psychology)) -- University of Limpopo, 2024
Keywords: Perceived vulnerability; Factor structure; Measurement invariance; Item loading; Attachment; Teenagers; Psychological tests; Diseases -- Social aspects; Attachment behavior; Communicable diseases; Vulnerability (Personality trait)